2016
DOI: 10.3857/roj.2016.01781
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of treatment outcomes for primary tonsillar lymphoma

Abstract: PurposeAlthough each Waldeyer’s ring sub-site is considered an independent prognostic factor, few studies have assessed the prognosis and treatment of tonsillar lymphoma. Treatment outcomes were analyzed in patients with primary tonsillar lymphoma who were treated with chemotherapy and radiotherapy (RT).Materials and MethodsNineteen patients with diffuse large B-cell lymphoma were evaluated, with a median follow-up of 53 months. Age, sex, and histology, amongst other factors, were reviewed. Progression-free su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…NHL of the head and neck is increasingly seen in patients above 50 years (1). Our study revealed that age of presentation of tonsil lymphoma was between 26-79 years of age, with a median age of 51 years and a male preponderance (male: female ratio of 3.33); this is comparable with other studies (2,4,5).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…NHL of the head and neck is increasingly seen in patients above 50 years (1). Our study revealed that age of presentation of tonsil lymphoma was between 26-79 years of age, with a median age of 51 years and a male preponderance (male: female ratio of 3.33); this is comparable with other studies (2,4,5).…”
Section: Discussionsupporting
confidence: 90%
“…Bulky disease is defined as primary tumour greater than 5 cm. in diameter (5) and occurs in 11% patients(4); the present study revealed bulky disease in 38.46%, the majority with late stage disease (stage III/ IV). The presence of bulky disease conferred lower OS (20%) when compared to smaller tumours (75%).…”
Section: Discussionsupporting
confidence: 50%
“…The 5-year PFS rates in the CHOP + RT (> 40 Gy) group vs. R-CHOP + RT (≤ 40 Gy) group were 50% vs. 100% ( P = 0.018) and 5-year OS rates were 66.7 %vs. 100% ( P = 0.087) [ 30 ]. RT dose reduction may be the trend for PT-DLBCL in the rituximab era especially for favorable good responders.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a direct comparison of oncologic outcomes between combined modality and chemotherapy alone groups was not available. [ 18 , 19 ] To verify our results, future multicenter trials are needed that will compare chemotherapy alone and chemotherapy plus radiotherapy methods for the treatment of DLBCL involving the head and neck.…”
Section: Discussionmentioning
confidence: 86%